(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The strength properties of concrete having self-curing agents as Polyethylene Glycol 400 are investigated in this paper. In this study self-curing agents is used with different amounts like 0, 0.5, 0.75, 1, 1.25, and 1.5 by weight of cement. In this study the cement content of 320 kgm3, watercement ratio of 0.55 is maintained. After casting cubes are subjected to self-curing during experiment for 28 days and are tested on 7 day, 14 day and 28 day. The results experiment indicates that, the use of self-curing agents in concrete effectively improved the mechanical properties. The self-curing concrete having polyethylene-glycol as self-curing agent, attained higher values of compressive strength properties. It was found that 1 of PEG 400 by weight of cement was optimum for M20, without compromising workability.